Optimum '1'-ended binary prefix codes - Berger, T.; Yeung, R.W. (IEEE transactions on information theory, 1990)
The problem of finding a binary prefix code of minimum average codeword length for a given finite probability distribution subject to the requirement that each codeword must end with a 1 is considered. Lower and upper bounds to the performance of the optimum code are derived; the lower bound is tight for certain probability distributions. An algorithm that generates an optimum code for any given distribution is described.< >